Three-dimensional modelling of slab-track systems based on dynamic experimental tests. (November 2021) - Thölken, D.; Abdalla Filho, J.E.; Pombo, J.; Sainz-Aja, J.; Carrascal, I.; Polanco, J.; Esen, A.; Laghrouche, O.; Woodward, P.
Abstract: The accurate computational modelling of railway systems is crucial for analysis and design, which allows for excellent and enduring performance of such systems. It is capable of providing the industry with data for improving speed, comfort, load capacity and reliability. Further, as accurate solutions serve as an aid to improve railway systems, they contribute to quality services, social welfare, cost effectiveness and sustainability. An important component of a railway system is the track, which, in general, requires high investments for construction and maintenance. This work develops calibrated three-dimensional (3D) Finite Element (FE) models for slab track systems which can be employed for analysis and design with great level of reliability. These models are developed based on full-scale dynamic tests performed under the application of loads which simulate the passage of high-speed trains. The components considered are the rails, rail pads, slab track, grout, Hydraulicaly Bonded Layer (HBL), Frost Protection Layer (FPL) and subgrade. The FE models are built and calibrated in order to reproduce the measured displacement and acceleration test results. Due to the uncertainties in some material properties, a parametric analysis is also performed to establish to which material characteristics of the system the model is more sensitive to. It has been found that the Young's moduli for the FPL layer and subgrade are the most important parameters. Further, the stiffness properties of rail pads play a paramount role in the accuracy of the model.